Development Of Auto Light Intensity Controller For Streetlights - Ahrveendraj a/l Munusamy (2023)
Streetlights to be turned on during daytime is one of the major problems in this era. Most of the time the streetlights are being turned on with full power supply during daytime which is unnecessary since there is no light need to be emitted by the streetlight during daytime which is assumed as a wastage of power and lots of fossil fuel is being burned to generate the power supply to the streetlight. Development of auto light intensity controller for streetlight would be a better solution for this problem. This prototype will automatically be turned on and off the streetlight during daytime and nighttime and emits required light depending about the area. This model for Auto Intensity Light Control with LED system using an Arduino UNO microcontroller with Pulse Width Modulation controller can set to be working at three conditions. First to be turned off during daytime. Next, is to work at half of its power during evening time. After that, to be working at full power during nighttime. This prototype works using an Arduino UNO microcontroller which controls the activity of the prototype. All the input data will be transferred to the circuit by using Pulse Width Modulation (PWM). The result of the experiment is for Auto Intensity Light Control with LED system using a Arduino UNO microcontroller with Pulse Width Modulation controller to work at the three different situation correctly so that wastage of power supply will not happen